2022
DOI: 10.1177/03635465211073148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Transforming Growth Factor–Beta 3 (TGF-β3) Loaded Nanoparticles on Healing in a Rat Achilles Tendon Injury Model

Abstract: Background: Achilles tendon (AT) midsubstance injuries may heal suboptimally, especially in athletes. Transforming growth factor–beta 3 (TGF-β3) shows promise because of its recently discovered tendinogenic effects. Using poly(lactic-co-glycolic acid)-b-poly(ethylene glycol) (PLGA-b-PEG) nanoparticles (NPs) may enhance the results by a sustained-release effect. Hypothesis: The application of TGF-β3 will enhance AT midsubstance healing, and the NP form will achieve better outcomes. Study Design: Controlled labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…The strategy of silencing PAI-1 instead of the upstream mediator TGF-β1 is preferable since TGF-β1 has some beneficial effects on tendon healing, such as the induction of cell proliferation and ECM formation. 39 Therefore, certain downregulation of TGF-β1 can be beneficial, but complete silencing is not desirable. Never-Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategy of silencing PAI-1 instead of the upstream mediator TGF-β1 is preferable since TGF-β1 has some beneficial effects on tendon healing, such as the induction of cell proliferation and ECM formation. 39 Therefore, certain downregulation of TGF-β1 can be beneficial, but complete silencing is not desirable. Never-Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The expression of Serpine1 is significantly downregulated when RAW 264.7 cells and PMA-differentiated THP-1 cells pretreated with TGF-β1 are treated with siRNA@LPNs and dual-loaded LPNs for 24 and 48 h, compared to the positive controls (TGF-β1 and LPS + TGF-β1, respectively) (Figures D and D). The strategy of silencing PAI-1 instead of the upstream mediator TGF-β1 is preferable since TGF-β1 has some beneficial effects on tendon healing, such as the induction of cell proliferation and ECM formation . Therefore, certain downregulation of TGF-β1 can be beneficial, but complete silencing is not desirable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 48 Previous studies have also demonstrated the potential effects of TGF-β3 on the tendinogenic differentiation of stem cells. 3 Recently, Cetik et al 8 reported the effectiveness of TGF-β3 on Achilles tendon healing in a rat model. The higher expression of these TGF-β isoforms in CG rats might have had a more favorable effect on tendon regeneration than that in NG rats.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b3 is well known for its antifibrotic effects. 8,48 Previous studies have also demonstrated the potential effects of TGF-b3 on the tendinogenic differentiation of stem cells. 3 Recently, Cetik et al 8 reported the effectiveness of TGF-b3 on Achilles tendon healing in a rat model.…”
Section: Discussionmentioning
confidence: 99%